2016
DOI: 10.1039/c6ra16188j
|View full text |Cite
|
Sign up to set email alerts
|

Noble gas supported B3+ cluster: formation of strong covalent noble gas–boron bonds

Abstract: Ar to Rn atoms formed exceptionally strong bonds with B3+, where the Ng (HOMO) → B3Ng2+ (LUMO) σ-donation is the key term to stabilize the complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 122 publications
1
27
0
Order By: Relevance
“…This success further inspired us to guess that the triangular, pentagonal and hexagonal ions normalB3+, normalB53+, and normalB64+ may also be good Rg trappers, which was certainly confirmed by our calculations . As we prepared our papers, we found that the triangular BRg compounds normalB3+Rgn+ ( n = 1, 2, 3, Rg = Ar ∼ Rn) had been reported in 2016 …”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This success further inspired us to guess that the triangular, pentagonal and hexagonal ions normalB3+, normalB53+, and normalB64+ may also be good Rg trappers, which was certainly confirmed by our calculations . As we prepared our papers, we found that the triangular BRg compounds normalB3+Rgn+ ( n = 1, 2, 3, Rg = Ar ∼ Rn) had been reported in 2016 …”
Section: Introductionsupporting
confidence: 74%
“…[40] As we prepared our papers, we found that the triangular BRg compounds B 1 3 Rg 1 n (n 5 1, 2, 3, Rg 5 Ar Rn) had been reported in 2016. [41] In this work, we will report our theoretical results about the planar rhombic BRg dications B 4 Rg 21 n (n 5 1-4, Rg 5 He Rn). The electronic structures and properties of the bare B 4 ring species such as B 4 , B 2 4 , and B 22 4 have been thoroughly studied, [28,42,43] but the B 21 4 dication receives no attention.…”
mentioning
confidence: 99%
“…Argon–boron containing compounds including FArBO, FArBF 2 and FArBN – were theoretically studied, and were predicted to be thermally metastable species with covalent Ar–B bonding. 19 Argon coordination complexes including ArBBAr, ArB + , ArBF 2 + and B 3 Ar 3 + have also been studied computationally, 20 – 23 and some of them exhibit remarkably strong Ar–B bonding. 22 , 23 Only the BAr + and ArBF 2 + cations as well as the metastable ArBF n 2+ dications have been experimentally detected using mass spectrometry in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Argon coordination complexes including ArBBAr, ArB + , ArBF 2 + and B 3 Ar 3 + have also been studied computationally, 20 – 23 and some of them exhibit remarkably strong Ar–B bonding. 22 , 23 Only the BAr + and ArBF 2 + cations as well as the metastable ArBF n 2+ dications have been experimentally detected using mass spectrometry in the gas phase. 24 , 25 Here we report the experimental preparation of a group of boron oxide–argon cation complexes in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Higher fluorides of krypton (KrF 4 , KrF 6 ) are not known (initial reports of the synthesis of KrF 4 [10,11] have never been confirmed), again in contrast to xenon which does form both XeF 4 and XeF 6 . Despite the mediocre reactivity of krypton a substantial number of compounds and complexes containing this element were speculated to exist in the gas phase [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%